The digital services of Brack Bank PLC, the opportunities challenges and the impact of digital transformation on customer interactions - khan, Shadman Zuhair (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2024.